Surface Characterization of Porous Ti-6Al-4V Dental Implant by Metal Injection Molding with Palm Stearin Binder System - J. B. Saedon; N. H. Mohamad Nor; M. H. Ismail; M. Newishy; Hazran Husain (International Journal of Integrated Engineering, 2024)
The osseointegration rate of Ti-6Al-4V dental implants is related to their composition and surface roughness. Rough-surfaced implants favour both bone anchoring and biochemical stability. This paper focused on the surface characteristic of highly porous Ti-6Al-4V dental implant by metal injection molding with palm stearin binder system with an addition of sodium chloride as space holder which has been established in the fabrication of porous Ti-6Al-4V. The integrated pores obtained on the dental implant provides the space for mineralized bone to growth and diffuse into the dental implant and improve the anchorage of the dental implant towards the bone and prevent dental implant loosening. The average surface roughness (Ra) of 4.62 ± 1.33 µm and 5.83 ± 1.25 µm was within the proposed ideal surface roughness of 1-10µm. In addition, the existence of lamellar of ?-? phase on the surface as-polished dental implant would improve both the mechanical as well as the elastic properties.